2000
DOI: 10.1096/fj.00-0292com
|View full text |Cite
|
Sign up to set email alerts
|

Halofuginone: a potent inhibitor of critical steps in angiogenesis progression

Abstract: We have previously demonstrated that halofuginone, a low molecular weight quinazolinone alkaloid, is a potent inhibitor of collagen alpha1(I) and matrix metalloproteinase 2 (MMP-2) gene expression. Halofuginone also effectively suppresses tumor progression and metastasis in mice. These results together with the well-documented role of extracellular matrix (ECM) components and matrix degrading enzymes in formation of new blood vessels led us to investigate the effect of halofuginone on the angiogenic process. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
83
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 34 publications
(76 reference statements)
7
83
0
3
Order By: Relevance
“…In prostate cancer and Wilms' tumor xenografts, halofuginone, but not the respective chemotherapies, affected collagen a1(I) gene expression and collagen content. These results are consistent with our previous findings that halofuginone inhibited collagen type I synthesis in various preclinical studies in which excess of collagen was the hallmark of the disease (20,21), and halofuginone-dependent inhibition of collagen type I synthesis was correlated with reduction in tumor progression (26,27). In addition, only halofuginone inhibited the synthesis of Cygb/STAP, which is known to regulate collagen synthesis under the control of TGF-h (18,19), a finding that is consistent with the notion that halofuginone acts through the inhibition of Smad2/3 phosphorylation downstream of TGF-h (22 -24).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In prostate cancer and Wilms' tumor xenografts, halofuginone, but not the respective chemotherapies, affected collagen a1(I) gene expression and collagen content. These results are consistent with our previous findings that halofuginone inhibited collagen type I synthesis in various preclinical studies in which excess of collagen was the hallmark of the disease (20,21), and halofuginone-dependent inhibition of collagen type I synthesis was correlated with reduction in tumor progression (26,27). In addition, only halofuginone inhibited the synthesis of Cygb/STAP, which is known to regulate collagen synthesis under the control of TGF-h (18,19), a finding that is consistent with the notion that halofuginone acts through the inhibition of Smad2/3 phosphorylation downstream of TGF-h (22 -24).…”
Section: Discussionsupporting
confidence: 93%
“…Cygb/STAP expression is upregulated under hypoxia and is regulated by the hypoxiainducible factor 1 (19), which regulates angiogenesis and is overexpressed in human cancers and their metastases (34). The inhibition of angiogenesis by halofuginone, in general (26), and of prostate cancer and Wilms' tumor xenografts, in particular (28,29), may suggest the involvement, at least in part, of hypoxia-inducible factor 1 -dependent Cygb/STAP overexpression in angiogenesis and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this report, we demonstrated that the angiogenetic response induced by bFGF is markedly reduced in mice lacking a functional gelatinase A gene compared with that of wildtype animals. Our data con¢rm the results reported by Elkin et al [12] who showed that halofuginone, an inhibitor of collagen K1(I) and gelatinase A gene expression, almost completely suppressed bFGF-induced angiogenesis in vivo and inhibited endothelial capillary tube formation in vitro.…”
Section: Discussionsupporting
confidence: 92%
“…18 The antiangiogenic effect of halofuginone has been described in several angiogenesis-dependent xenografts models. [18][19][20] For the first time, our data demonstrate that proangiogenic effect of Col(I) expression contributes to the angiogenic switch that subsequently facilitates the progression of microinvasive to deeply invasive tumors in a de novo melanoma model. …”
mentioning
confidence: 99%